Protesting Precarity: South Korean Workers and the Labor of Refusal - Chun, Jennifer Jihye (The Journal of Asian studies, 2022)
This essay examines the crisis of solidarity affecting workers who protest labor precarity under South Korea's capitalist democracy. Once considered foundational to the struggle for national democratization, the dramatic protests of aggrieved workers are frequently depicted as out of place and out of sync. Drawing upon ethnographic research on workers’ protest repertoires, this essay challenges prevailing explanations and instead argues that heightened forms of drama, ritual, and suffering in workers’ protests enact a willful politics of refusal. Moving beyond resistance as an all-encompassing frame, the labor of refusal foregrounds ways of being and becoming that are not rooted in the contractual fallacies of liberal capitalist democracy, but in the spaces of solidarity produced by social movement networks and grassroots communities of care. The labor of refusal may not always generate robust solidarity, but it challenges the structures of organized abandonment that treat workers as disposable under neoliberal capitalist rule.